Efektivitas Orthosiphon Stamineus sebagai terapi komplementer hipertensi: Tinjauan sistematik - Maulina, Devi (PT WIM Solusi Prima, 2025)
Hypertension remains a global health concern demanding effective, affordable, and safe treatment alternatives. Orthosiphon stamineus Benth. (Java tea) has long been used traditionally to manage elevated blood pressure, yet no systematic review has comprehensively evaluated its efficacy and safety. This study aims to synthesize experimental and clinical evidence on the antihypertensive effects, mechanisms of action, and safety profile of O. stamineus. A systematic literature search was conducted using PubMed, Scopus, and ScienceDirect with the keywords “Orthosiphon stamineus,” “hypertension,” “blood pressure,” and related study designs. Article selection followed PRISMA guidelines, and risk of bias was assessed using SYRCLE for animal studies and RoB 2 for clinical trials. Twenty three relevant studies met the inclusion criteria, revealing consistent blood pressure-lowering effects through diuretic activity, inhibition of angiotensin-converting enzyme (ACE), and vasorelaxation via endothelial nitric oxide pathways. However, substantial heterogeneity in extraction methods, doses, and study designs limits conclusive generalization. The findings suggest that O. stamineus holds promise as a complementary therapy for hypertension, although further robust clinical trials are necessary to confirm its clinical utility. Hipertensi merupakan masalah kesehatan global yang membutuhkan alternatif terapi yang efektif, aman, dan terjangkau. Orthosiphon stamineus (Kumis Kucing) telah lama digunakan secara tradisional untuk mengatasi tekanan darah tinggi, namun belum ada tinjauan sistematik yang mengevaluasi efektivitas dan keamanannya secara menyeluruh. Penelitian ini bertujuan untuk mensintesis bukti eksperimental dan klinis terkait efek antihipertensi, mekanisme kerja, dan profil keamanan O. stamineus. Pencarian literatur dilakukan secara sistematik pada basis data PubMed, Scopus, dan ScienceDirect dengan kata kunci (